The foreign policy of Soviet Russia : report (Nov. 1918 tot Dec. 1919) - People's Commissary for Foreign Affairs to the Seventh All-Russian Congress of Soviets (London : Northampton Press, 1920)
Fonds Perrone
Engels
Brochure
Keywords: buitenlandse politiek; Rusland